(untitled) (Studia theodisca, 2012)
Pop songs can be used as semiotic signs to give insight into public opinion simply because they have to prove themselves successfull in a commercial environment: they should reflect, not contradict, the general attitudes of the song’s buyers. In this article I will refer to the song «Männer» by Herbert Grönemeyer, questioning whether its text really breaks with traditional role models. I come to a somewhat qualifying answer. However, especially since Grönemeyer does not contradict the old role model, he seems to be credible when he ignores it in his later song «Mensch».